2017
DOI: 10.35313/jbit.v3i2.1263
|View full text |Cite
|
Sign up to set email alerts
|

Using Componential Analysis to Evaluate Translation Results

Abstract: Componential analysis is an analysis of the meaning of a word by breaking down the word into different pieces called 'component parts'. This kind of analysis could be helpful in the process of translation to choose the most accurate and closest lexical equivalents. This study aims to weigh the use of componential analysis for evaluating the accuracy of the translated words. The data are five Indonesian dish names and their English translation printed on the packaging of instant spices. The study proves that by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The data in number (1)(2)(3)(4) are taken from the same novel and it discusses the same kind of sambal made mostly of green chili mixed with red chili and it tastes very hot that it needs time to get rid of the spiciness from our mouth that you need to take a rest a bit before continuing with your other activities. It is therefore it is called sambal istirahat 'rest'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in number (1)(2)(3)(4) are taken from the same novel and it discusses the same kind of sambal made mostly of green chili mixed with red chili and it tastes very hot that it needs time to get rid of the spiciness from our mouth that you need to take a rest a bit before continuing with your other activities. It is therefore it is called sambal istirahat 'rest'.…”
Section: Resultsmentioning
confidence: 99%
“…The seventh previous research is a journal article about the translation of five popular traditional foods in Indonesia using componential analysis. Its aims are to find out the accuracy of the translation and giving option of possible translation techniques to overcome the difficulty in translating the names of food as cultural words (Dewiyanti & Suryani, 2017). The last previous research is a journal article about translating traditional food from West Java, the data analysis involves translation procedures by Newmark and the result shows that most appropriate translation procedure for translating traditional food is cultural equivalent (Amalia, 2017).…”
Section: A Previous Researchesmentioning
confidence: 99%
“…Many studies tackle one of the two theoretical bases, suggested in the present study. As for the componential analysis, Belfarhi (2013), Dewiyanti and Suryani (2017), and Al-Abbas and Khanji (2019) analyzed significant lexemes into their possible semantic units for various research purposes. Belfarhi (2013) applied the tools to literary English texts in order to make a small dictionary, with some componential analysis approach.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Dewiyanti and Suryani (2017) compared the semantic components of five Indonesian dish names to their English translations, and presented the statistical findings to recommend the closest English translation. Al-Abbas and Khanji (2019) attempted the terms c ām ‫عام‬ and sana(t) ‫َة‬ ‫ن‬ َ ‫س‬ in the respective verses of the Holy Qur'an and in five selected translations, highlighting the appropriate TT.…”
mentioning
confidence: 99%